2022
DOI: 10.21037/atm-22-6054
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of neoadjuvant pertuzumab plus trastuzumab in combination with chemotherapy regimen in Chinese patients with HER2-positive early breast cancer: a real-world retrospective multi-center cohort study

Abstract: Background: Pertuzumab plus trastuzumab combined with chemotherapy has become a standard neoadjuvant therapy option for patients with high-risk human epidermal growth factor receptor 2 (HER2)positive breast cancer (BC). There is still not enough evidence for the efficacy and safety of neoadjuvant pertuzumab and trastuzumab plus chemotherapy in HER2-positive BC patients in China, both in clinical trials and real-world settings. This study aimed to assess the efficacy and safety of neoadjuvant pertuzumab plus tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This trial observed no death in patients given the neoadjuvant treatment, and grade 3 and 4 neutropenia and febrile neutropenia occurred in 12% and 8% of patients, respectively [21]. A retrospective study on pertuzumab, trastuzumab, and chemotherapy showed that this treatment regimen had a tolerable safety profile and that anemia was the most common adverse event (63.4%) observed in the study, and the most common grade 3-4 adverse event was nausea and vomiting (8.5%) [22]. A study on the safety and efficacy of pertuzumab in the treatment of HER2-positive breast cancer showed that although the most common side effect associated with the use of pertuzumab was diarrhea, most cases were not severe.…”
Section: Discussionmentioning
confidence: 92%
“…This trial observed no death in patients given the neoadjuvant treatment, and grade 3 and 4 neutropenia and febrile neutropenia occurred in 12% and 8% of patients, respectively [21]. A retrospective study on pertuzumab, trastuzumab, and chemotherapy showed that this treatment regimen had a tolerable safety profile and that anemia was the most common adverse event (63.4%) observed in the study, and the most common grade 3-4 adverse event was nausea and vomiting (8.5%) [22]. A study on the safety and efficacy of pertuzumab in the treatment of HER2-positive breast cancer showed that although the most common side effect associated with the use of pertuzumab was diarrhea, most cases were not severe.…”
Section: Discussionmentioning
confidence: 92%
“…Subgroup analyses demonstrated that there was no signi cant difference in pCR rate among the neoadjuvant chemotherapy regimens in the population with ER+, PR+, HER2 IHC 2+, and Ki67 index < 30%. This indicates that for patients with these characteristics, THP can be used as an alternative to the TCbHP regimen, when taking the high incidence of grade 3-4 thrombocytopenia observed with TCbHP compared to THP into account 31 . However, for ER-PR-HER2-positive patients, the neoadjuvant chemotherapy regimen has a great in uence on the pCR rates.…”
Section: Discussionmentioning
confidence: 99%